PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN AIR MINERAL MEREK MINUMO PADA CV. JAYA ABADI SEJAHTERA CABANG CIREBON - Tuwuh Bayu Aji; Purwanti (Journal of Research and Publication Innovation, 2025)
This study aims to examine the influence of price and service quality on customer satisfaction at CV. Jaya Abadi Sejahtera, Cirebon branch. The research utilizes a quantitative analysis method with an associative approach. The population consists of 11,760 customers of the Cirebon branch, with a sample size of 99 respondents determined using the Slovin formula. The sampling method applied is non-probability sampling, specifically accidental sampling. Data analysis techniques include descriptive analysis, instrument testing, classical assumption tests, correlation and determination tests, as well as hypothesis testing. The findings reveal that price (X1) has a positive and significant impact on customer satisfaction (Y), supported by the t-test results showing t_calculated > t_table (7.775 > 1.984). This is further confirmed by a p-value < 0.05 (0.000 < 0.05), leading to the rejection of H0 and acceptance of H1, indicating a positive and significant effect of price on customer satisfaction. Similarly, service quality (X2) also positively and significantly affects customer satisfaction (Y), as evidenced by the t-test results where t_calculated > t_table (5.414 > 1.984), along with a p-value < 0.05 (0.000 < 0.05). Consequently, H0 is rejected and H1 is accepted, demonstrating the significant influence of service quality on customer satisfaction. Moreover, both price (X1) and service quality (X2) have a simultaneous positive and significant effect on customer satisfaction (Y), as shown by the F-test results, with F_calculated = 29.307 > F_table = 3.090 and a probability value of 0.000 < 0.05. Thus, H0 is rejected and H3 is accepted, confirming the combined significant influence of price and service quality on customer satisfaction.